Serum TNF-α and IL-1β levels in patients with RNFL thinning in uveitis complicated by optic nerve inflammation - M. V. Panchenko; M. M. Nikolaienko; O. M. Honchar; D. O. Prykhodko; H. S. Pereiaslova; O. O. Sokol (Journal of Ophthalmology, 2020)
Purpose: To assess serum tumor necrosis factor-alpha (TNF-α) and interleukin-1β (IL-1β) levels in patients with retinal nerve fiber layer (RNFL) thinning in uveitis complicated by optic nerve inflammation.